Clinical characteristics, risk factors and pre‐surgical evaluation of post‐infectious epilepsy. Issue 3 (4th September 2012) - Sellner, J.; Trinka, E.
Abstract : Background and purpose: Epilepsy is a frequent complication of central nervous system (CNS) infections. Post‐infectious epilepsy is commonly refractory to medical treatment and plays a pivotal role for the poor long‐term outcome of CNS infections. Objectives: To provide an overview of clinical characteristics and risk factors of seizures associated with CNS infections. In addition, to summarize the state of the art of anticonvulsive treatment and the pre‐surgical evaluation process in refractory cases. Methods: A comprehensive literature search for articles published between January 1970 and December 2011 was carried out. Results: The occurrence of seizures during the acute course of meningitis, encephalitis and brain abscess is the main risk factor for the development of post‐infectious epilepsy. There is a shortage of trials evaluating the efficacy of prophylactic and symptomatic treatment during the course of acute infection. Moreover, there are no randomized‐controlled trials studying anticonvulsive drugs and their combinations for the management of post‐infectious epilepsy. In a selected group of patients, however, medically refractory focal epilepsy is potentially curable by surgery. Conclusions: Further studies are required to improve the pathogenetic understanding of post‐infectious epilepsy in order to develop preventive measures as well as to evaluate additional medical and surgical treatment strategies for the patients currently not considered for surgery.